The Effect of Stand Location and Booth Design on Purchase Decisions Through Positive Emotion - Muzdalifah, Laily; Larassaty, Ayu Lucy; Sholichah, Umniyah Mar’atun (SENTRALISASI, 2021)
This study is aimed to determine the effect of stand location and booth design on purchasing decisions through positive emotion. This research is a quantitative research using descriptive approach. The research sample is 100 respondents. The research setting is at wedding events that held in Icon Mall Gresik, MOG Malang and CITO Surabaya. The sample was taken by accidental sampling method, while the data collection technique used a questionnaire, documentation and observation. Data analysis technique using Path Analysis. The results shows that; 1) Stand location had an effect on positive emotion, 2) Booth design had an effect on positive emotion, 3) Positive emotion had an effect on purchasing decisions, 4) Stand location had an effect on purchasing decisions, 5) Booth design had an effect on purchasing decisions, 6) Stand location affects the purchasing decisions through positive emotions, 7) Booth design affects purchasing decisions through positive emotions.